Comparison of endoscopy and C-14 urea breath test in terms of helicobacter pylori positivity in patients admitted with complaints of dyspepsia - Celal Kilit; İlknur Işık; Türkan Kilit; Yasemin Korkut (SERNEV, 2016)
Introduction: In this study, we aimed to compare Carbon-14 Urea Breath Test (C-14 UBT) and endoscopy in diagnosis of Helicobacterpylori (HP) and show the availability of the C-14 UBT in follow-up.Methods: We enrolled 183 patients who were admitted to Dumlupınar University Faculty of Medicine, Kütahya Evliya ÇelebiEducation and Research Hospital between April 2012-February 2015 with dyspeptic complaints and C-14 UBT performed due to thesuspicion of HP infection. Patient records were analyzed retrospectively.Results: We enrolled 183 patients with age range 7-71 years. The mean age was 31 ± 15 years and 129 of patients were female (7%),and 54 were male (30%). According to the results of C-14 UBT, HP was negative in 77 of patients (42%), HP was probable in 2 ofpatients (1%) and HP was positive in 104 patients (57%). There was no significant difference between HP positive and HP negativegroups in terms of age and gender. When compared the results of C-14 UBT with upper gastrointestinal system endoscopy, it was foundthat there was no difference between the two methods for the determination of the HP positivity (p gt;0.05).Conclusion: C-14 UBT is a reliable, noninvasive and practical test which can be used in the diagnosis of HP.